Професійна підготовка фахівця машинобудівних підприємств з підвищення міцнісних характеристик виробів, отриманих методом адитивного виробництва за п'ятиосьовою технологією FDM - Осипенко, Владислав Олегович (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Кваліфікаційна робота присвячена науковому обґрунтуванню та вдосконаленню системи підготовки фахівців машинобудівних підприємств з підвищення міцнісних характеристик виробів, отриманих методом адитивного виробництва за п'ятиосьовою технологією FDM. Розглянута актуальність професійної підготовки фахівця машинобудівних підприємств з підвищення міцнісних характеристик виробів, отриманих методом адитивного виробництва за п'ятиосьовою технологією fdm. Проаналізовано способи виробництва виробів з полімерних композиційних матеріалів в аддитивних технологіях, розроблено теоретичні основи технології п'ятиосьового друку з армуванням та практичну реалізацію технології п'ятиосьового друку з армуванням. Запропонована методика може бути покладена в основу інноваційних технологій під час навчання для отримання кваліфікованих фахівців машинобудівної галузі.

The qualification work (diploma project) is devoted to the scientific substantiation and improvement of the system of training specialists of machine building enterprises to increase the strength characteristics of products obtained by the additive manufacturing method using five-axis FDM technology. The first section considers the relevance of professional training of specialists of machine-building enterprises to increase the strength characteristics of products obtained by the additive manufacturing method using five-axis FDM technology. The second section analyzes the methods of manufacturing products from polymer composite materials in additive technologies. In the third section, the development of theoretical foundations of the technology of five-axis printing with reinforcement is carried out. In the fourth section, the practical implementation of the technology of five axis printing with reinforcement. In the fifth section, experimental studies of the influence of cutting modes on the output parameters. The proposed methodology can be used as the basis for innovative technologies during training to obtain qualified specialists in the mechanical engineering industry.
Professional training of specialists of machine-building enterprises to increase the strength characteristics of products obtained by the additive manufacturing method using five-axis FDM
Керівник роботи: Скоркін Антон Олегович, кандидат технічних наук, доцент кафедри машинобудування, транспорту і зварювання Навчально-наукового інституту «Українська інженерно-педагогічна академія»
Keywords: TECHNOLOGY::Engineering mechanics::Mechanical manufacturing engineering; SOCIAL SCIENCES::Social sciences::Education::Subject didactics; машинобудівна галузь; професійна підготовка; фахівець; адитивне виробництво; полімерні композити; professional training; mechanical engineering industry; specialist; additive manufacturing; polymer composites